Influence of various concentrate‐to‐roughage ratios on dietary intake and nutrient digestibilities of weanling horses. Issue 1 (23rd October 2018) - Turcott‐White, Susan K.; Nielsen, Brian D.; Robison, Cara I.; Skelly, Christine D.; Rosenstein, Diane S.; Pritchard, Abby; Herdt, Thomas
Abstract: The objective of this study was to compare the feed intake and the apparent digestibilities of three different diets varying in concentrate‐to‐roughage ratios in weanling horses ( n = 24) at 5 and 8 months of age. Horses were stratified by breed, gender, birth date and body weight and assigned to one of three dietary treatments containing the following concentrate‐to‐roughage ratios on an as‐fed basis: 70:30 (High Con), 50:50 (Equal) and 30:70 (Low Con). All horses were fed their respective diets for a 10‐day adaptation period and a 4‐day collection period at 5 and 8 months. There were no differences in BW or daily feed intake among treatments during both trials. The horses consuming Low Con had a greater amount of faecal output than High Con at both 5 and 8 months ( p < 0.01). At 5 months, High Con had the highest crude protein (CP) digestibility ( p < 0.05). At 8 months, High Con had a higher CP digestibility than Low Con ( p < 0.01) and tended to be higher than Equal ( p = 0.07). Acid detergent fibre (ADF) digestibility did not differ among treatments; however, horses fed the Low Con tended to digest a higher percentage of neutral detergent fibre (NDF) than both the Equal and High Con treatments ( p = 0.09). Horses in the High Con treatment tended to digest a higher percentage of energy than those in the Low Con treatment ( p = 0.06). Weanlings seem to digest protein more thoroughly when fed high‐concentrate diets and may digest fibre more efficiently when fed diets higher in fibre.